Training Improves Vibrotactile Spatial Acuity and Intensity Discrimination on the Lower Back Using Coin Motors. Issue 11 (1st June 2017) - Stronks, H. Christiaan; Walker, Janine; Parker, Daniel J.; Barnes, Nick
Abstract: Tactile vision substitution devices are assistive technologies for the blind that redirect visual information to the tactile sense. They typically include a tactile display that conveys visual information to the skin. Two important parameters that determine the maximum information bandwidth of tactile displays are the spatial acuity of the skin, and the ability of the user to discriminate between stimulus intensities. These two parameters were investigated by determining the two‐point discrimination (TPD) threshold and the just‐noticeable intensity difference (JND) using coin motors on the lower back. Coin motors are eccentric rotating‐mass motors that are affordable, energy‐efficient, and easy to implement. The lower back was chosen because it is a discreet place to wear assistive technology. It is generally available for use, as it is usually not critically involved in activities of daily living. Rehabilitation with sensory substitution devices often requires training by professional occupational therapists, because the user needs to extract visual information from sparse information presented through an alternative channel such as the skin. In this study they determined whether short, automated training sessions of 5 min each could improve the TPD threshold and JND. It was found that 10 min of computer‐assisted training improved the vibrotactile TPD threshold on the lower back by 36%, and that 18 min of training improved the just‐noticeable intensity difference (JND) by 44%. It was concluded that short, automated training sessions could provide a fast and inexpensive means to improve people's basic spatial acuity and intensity discrimination skills with coin motors.